Acute Hepatic Allograft Rejection in Pediatric Recipients: Independent Factors - SM Dehghani; I Shahramian; M Afshari; M Bahmanyar; M Ataollahi; A Sargazi (International Journal of Organ Transplantation Medicine, 2017)
Background: Acute cellular rejection (ACR) has a reversible effect on graft and its survival.